2012
DOI: 10.1186/1471-2482-12-15
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the length of the incision and the operating time for total thyroidectomy

Abstract: BackgroundThe incision used for thyroid surgery has become shorter over time, from the classical 10 cm long Kocher incision to the shortest 15 mm access achieved with Minimally Invasive Video-Assisted Thyroidectomy. This rather large interval encompasses many different possible technical choices, even if we just consider open surgery.The aim of the study was to assess the correlation between incision length and operation duration with a set of biometric and clinical factors and establish a rationale for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
2
18
1
1
Order By: Relevance
“…For example, Consorti and colleagues examined the factors influencing operating time for total thyroidectomy. They found that factors such as thyroid volume or neck circumference explained very little of the variance in operative time (39). Increased gland size is traditionally viewed as a factor contributing to difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Consorti and colleagues examined the factors influencing operating time for total thyroidectomy. They found that factors such as thyroid volume or neck circumference explained very little of the variance in operative time (39). Increased gland size is traditionally viewed as a factor contributing to difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not examine the trauma of skin edges during thyroidectomy as a potential risk factor for hypertrophic scarring. However, these and other authors have highlighted the importance of avoiding excessive retraction, trauma or thermal injury to the skin edges during the execution of the operation in order to achieve a better cosmetic result 4,5,8,10,11 . To our knowledge, there is only one formally published technique for skin protection in thyroid surgery.…”
Section: Surgical Technique Surgical Technique Surgical Technique Surmentioning
confidence: 99%
“…Therefore, it is essential to achieve the best cosmetic result in the classic open thyroidectomy scar, since the procedure is indicated for most patients. For this, several technical solutions have been proposed, such as prethyroid muscles section and thyroidectomy without detaching the skin flap 4 . Currently, conventional thyroidectomy is performed through an anterior necklace incision in the neck, two to three inches above the sternal notch, preferably on a natural neck fold or wrinkle, with a length ranging from four to six inches, depending on the anatomical characteristics of the patient (neck circumference) and the size of the gland to be removed 4 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be extended to all structures dissected during the procedure [2]. Although there has been some work studying minimally invasive head and neck surgeries [3,4], our search revealed little literature available regarding minimally invasive techniques being applied to open surgical tracheostomy [5,6].…”
Section: Introductionmentioning
confidence: 99%